How can open innovation contribute to circular economy adoption? Insights from a literature review - Jesus, Gessica Mina Kim [UNESP]; Jugend, Daniel [UNESP] (Emerald, 2021)
Purpose: Despite the potential of open innovation (OI) to reduce barriers to the adoption of the circular economy (CE), little is known about the integration of the two themes and how OI could contribute to a more sustainable economy. The objective of this study is to investigate how OI can contribute to the adoption of the CE. Design/methodology/approach: This study adopts a systematic review of the literature sampled from the Scopus and Web of Science scientific databases. Findings: The main findings of the study are (1) the utilization of OI within CE is still a recent phenomenon, one which emphasizes the collaboration between stakeholders and the co-creation approach; (2) the collaboration of stakeholders can be applied to align the objectives of interested parties, in a joint effort to resolve the environmental problems of the three levels of CE and (3) an action-creation approach can be adopted as a strategy to encourage the participation of consumers in the development of environmentally sustainable products, which may favor the transition to the CE. Originality/value: The article presents the state of the art on the CE guided by OI, highlighting the opportunities and challenges of the correlation between the two themes. The article also shows the theoretical and practical implications for an OI-driven circular economy.
Keywords: Circular economy; Circular oriented innovation; Open innovation; Sustainability